Community-led and/or focused initiatives to support family carers within a palliative care context: An integrative review. (February 2019) - Chung, Anita; Collier, Aileen; Gott, Merryn
Background: Public health approaches to palliative care prioritise community-focused initiatives to support people with palliative care needs and their families. The nature and extent of these initiatives have not previously been reported. Aim: To identify community-led and/or focused initiatives that have been developed to support family carers of people with palliative care needs and for which evaluation information is reported in the empirical literature. Design: An integrative study design was undertaken using systematic methods. Data sources: CINAHL, Medline, PsycINFO, Embase, Cochrane, Sociological Abstracts, Proquest Social Science Database, and grey literature were searched using standardised search terms. Results: Two quantitative, two qualitative and two mixed method studies were identified ( n  = 6). All community initiatives identified were professionally led, although three had consumer input. Most aimed to improve carer psychosocial well-being and all were reported to have been beneficial. Conclusions: This integrative review identified only six community-focused and evaluated initiatives supporting family carers in the international palliative care research literature. Further evaluation is needed. However, appropriate evaluation methods and reporting require further discussion and debate between all stakeholders. Service users and communities themselves must be central to this process.